Variation of thermal plasticity in growth and reproduction patterns: Importance of ancestral and developmental temperatures. (August 2019) - Loisel, Ayala; Isla, Alejandro; Daufresne, Martin
Abstract: Temperature is an important ecological driver modulating life history traits of organisms, such as growth and reproduction. With the ongoing global warming, understanding the mechanisms underlying the effect of temperature on size and resource allocation trade-off is crucial. The temperature-size rule (TSR) describes plastic growth patterns in populations of ectothermic species under different thermal environments, whereby warming results in faster initial growth but lower size at maturity. However, the evolution of the TSR remains poorly understood. Here we conducted an experiment with populations of the medaka fish Oryzias latipes maintained at two temperatures for successive generations to investigate changes in the growth pattern of the TSR. After rearing six generations at cold (20 °C) and warm (30 °C) temperature, we conducted common garden experiments on the seventh generation where we compare growth trajectories and reproduction patterns in four different groups of fish: (i) fish reared at cold temperature over all seven generations (cold past and present), (ii) fish reared at warm temperature over six generations and at cold temperature at the seventh generation (warm past and cold present), (iii) fish reared at warm temperature over all seven generations (warm past and present) and (iv) fish reared at cold temperature over six generations and at warm temperature at the seventh generation (cold past and warm present). For each treatment, we monitored growth curves and reproduction, and investigated changes in model parameters and reproduction up to 350 days after hatching. Our study showed changes in TSR patterns according to ancestral and developmental temperatures. Developmental temperature mainly impacted age at maturity and asymptotic size, whereas size at maturity was driven more by the dissimilarity between developmental and ancestral temperatures. Our results also highlight a loss of plasticity in temperature-size and reproductive patterns for the fish that were reared under warm condition over six generations. Highlights: Patterns of the TSR persisted over generation but varied according to thermal ancestral and developmental conditions. Fish from crossed treatment showed lower final size than fish from homogeneous lines sharing developmental temperature. Individuals with same ancestral and developmental temperature evolved toward "slow/cold" ecological strategies. Individuals enduring warming exhibited an extreme warm-type TSR strategy suggesting a "plastic overshoot". Individuals enduring cooling presented lower amplitude of response suggesting a potential loss of plastic abilities.